Financial Infusion and Exiting from a Money Rule - Stone, Mark (IMF Working Papers; Working Paper ;, 1998)
Money demand often surges after successful macroeconomic stabilization. This paper gives a name-financial infusion-to these surges because their size, unpredictability, and concurrence with other 'success shocks' pose unique challenges to policy, especially under a money rule. An examination of 26 stabilization episodes shows that money to GDP can be expected to decline before stabilization and rise sharply thereafter. Analysis of the policy response to financial infusion under a money rule concludes that it amplifies output and price volatility, even if built into the rule. Finally, the main elements of an exit strategy from a money rule to an exchange rate or inflation target are discussed.